(untitled) (The Pakistan Development Review, 1992)
Round about the mid-1970s it came to be realised that the fruits of development were not being distributed widely. In fact, in a growing number of instances, the benefits of development were being limited to the elites in the developing countries - the vast majority of the population was being side-stepped. As a consequence of this happening, questions began to be raised: Why had such a situation developed? One possible and quite plausible answer was that the development process had ignored people’s participation. This, then, became the keyword. Two strands of thinking developed from the use of this word: the first highlighted the inclusion of human resources in the process of development; the second was more political in nature because poor people have very little say in the matters that influence their earning ability. To surmount this situation requires a structural change by which the poor can be directly included in the development process, so that they will gain some control over the resources, which would then enable them to have a higher standard of living.